(untitled) (Nigerian Journal of Physiological Sciences, 2025)
Phenylhydrazine (PHZ) triggers oxidative stress through the generation of reactive oxygen species and lipid peroxidation, resulting in organ and DNA damage. Kolaviron (KV), a biflavonoid complex extracted from Garcinia kola seeds, has shown properties that combat oxidative stress and protect cells. Aim was to evaluate the protective effects of kolaviron against phenylhydrazine-induced hepatotoxicity, splenic pathology, and genotoxicity in Wistar rats. Twenty-eight male rats were divided into four groups: Control (distilled water), PHZ (40 mg/kg intraperitoneally for 3 days), PHZ+KV (PHZ at 40 mg/kg+KV at 100 mg/kg orally for 14 days), and KV alone (100 mg/kg orally for 14 days). Hepatotoxicity, splenic pathology, and genotoxicity were assessed via biochemical analyses, oxidative stress markers, antioxidant parameters, histopathology, and micronucleus testing in bone marrow cells. Results showed PHZ significantly elevated liver enzymes (p<0.05), increased malondialdehyde levels, decreased antioxidant enzymes, and caused periportal fibrosis. Treatment with KV normalized these liver parameters and mitigated histopathological damage. In the spleen, PHZ induced lymphoid follicular hyperplasia, whereas in the PHZ+KV group, we observed lymphoid follicular necrosis; nonetheless, splenic oxidative stress and antioxidant levels remained similar across all groups. For genotoxicity, PHZ significantly increased micronucleated polychromatic erythrocytes and reduced the polychromatic erythrocytes/normochromatic erythrocytes ratio (p<0.05), while KV treatment restored these to near-control levels. Kolaviron showed significant hepatoprotective and genoprotective effects against PHZ-induced toxicity, primarily through modulation of oxidative stress parameters, though its impact on splenic pathology was weak. Further research should investigate the best dosing regimens and molecular mechanisms underlying KV’s protective effects against oxidative damage. Keywords: Kolaviron, Phenylhydrazine, Hepatotoxicity, Genotoxicity, Oxidative stress, splenic pathology